KONSEP DAN MANAJEMEN DAKWAH ISLAM DI ERA DIGITAL - Azis Sudiyat, Muhammad; Solahuddin, Solahuddin (Moderation | Journal of Islamic Studies Review, 2023)
The machine is a vital part, with several supporting tools that can move massively to produce aprocess, namely solid and perfect goods. So if the machine is not managed properly some of the supportingtools will move erratically or can damage some production results. Like a machine, da'wah is a major partin producing buds that always spread the religion of Islam. Da'wah is also the engine or soul for Islamicteachings on earth. According to the Big Indonesian Dictionary, the concept means; understanding, mentalimage of the object, process, opinion (understanding), design (aspirations) that has been thought of.Management basically does not have a standard and fixed definition that is universally agreed upon.However, Ricky W. Griffin defines management as a process of planning, organizing, coordinating, andcontrolling resources to achieve goals (goals) effectively and efficiently. Effective means that goals can beachieved according to planning, while efficient means that existing tasks are carried out correctly, organizedand according to schedule. A new era brings new weapons, that is what Tan Malaka said in his book, HisYouthful Spirit. Each era has its own characteristics. This characteristic brings two things, either glory ordamage. The Da'wah of Islam brought by the Most Beautiful Man, the Most Noble Man, namely HisMajesty the Prophet Muhammad Saw, is an activity that brings light to darkness, delivers freedom fromslavery, delivers faith from polytheism. After His Majesty Saw passed away to Rahmatullah, IslamicDa'wah continued with His Companions Saw. Executed with the guidance that has been exemplified byHis Majesty, do not change the teachings even if one letter. However, the Companions who stopped by intheir respective times had several social methods that were applied to the Muslims so that the light deliveredby His Majesty would remain intact and be conveyed even though the times had brought their characteristicswhich might lead to damage on earth.